The contribution of the voluntary sector to mental health crisis care: a mixed-methods study - Karen Newbigging; James Rees; Rebecca Ince; John Mohan; Doreen Joseph; Michael Ashman; Barbara Norden; Ceri Dare; Suzanne Bourke; Benjamin Costello (National Institute for Health Research, 2020)
Background: Weaknesses in the provision of mental health crisis support are evident and improvements that include voluntary sector provision are promoted. There is a lack of evidence regarding the contribution of the voluntary sector and how this might be used to the best effect in mental health crisis care. Aim: To investigate the contribution of voluntary sector organisations to mental health crisis care in England. Design: Multimethod sequential design with a comparative case study. Setting: England, with four case studies in North England, East England, the Midlands and London. Method: The method included a scoping literature review, a national survey of 1612 voluntary sector organisations, interviews with 27 national stakeholders and detailed mapping of the voluntary sector organisation provision in two regions (the north and south of England) to develop a taxonomy of voluntary sector organisations and to select four case studies. The case studies examined voluntary sector organisation crisis care provision as a system through interviews with local stakeholders (n = 73), eight focus groups with service users and carers and, at an individual level, narrative interviews with service users (n = 47) and carers (n = 12) to understand their crisis experience and service journey. There was extensive patient and public involvement in the study, including service users as co-researchers, to ensure validity. This affected the conduct of the study and the interpretation of the findings. The quality and the impact of the involvement was evaluated and commended. Main findings: A mental health crisis is considered a biographical disruption. Voluntary sector organisations can make an important contribution, characterised by a socially oriented and relational approach. Five types of relevant voluntary sector organisations were identified: (1) crisis-specific, (2) general mental health, (3) population-focused, (4) life-event-focused and (5) general social and community voluntary sector organisations. These voluntary sector organisations provide a range of support and have specific expertise. The availability and access to voluntary sector organisations varies and inequalities were evident for rural communities; black, Asian and minority ethnic communities; people who use substances; and people who identified as having a personality disorder. There was little evidence of well-developed crisis systems, with an underdeveloped approach to prevention and a lack of ongoing support. Limitations: The survey response was low, reflecting the nature of voluntary sector organisations and demands on their time. This was a descriptive study, so evaluating outcomes from voluntary sector organisation support was beyond the scope of the study. Conclusions: The current policy discourse frames a mental health crisis as an urgent event. Viewing a mental health crisis as a biographical disruption would better enable a wide range of contributory factors to be considered and addressed. Voluntary sector organisations have a distinctive and important role to play. The breadth of this contribution needs to be acknowledged and its role as an accessible alternative to inpatient provision prioritised. Future work: A whole-system approach to mental health crisis provision is needed. The NHS, local authorities and the voluntary sector should establish how to effectively collaborate to meet the local population's needs and to ensure the sustainability of the voluntary sector. Service users and carers from all communities need to be central to this. Funding: This project was funded by the National Institute for Health Research (NIHR) Health Services and Delivery Research programme and will be published in full in Health Services and Delivery Research; Vol. 8, No. 29. See the NIHR Journals Library website for further project information.